2022
DOI: 10.1007/s00018-022-04288-0
|View full text |Cite
|
Sign up to set email alerts
|

Impaired primordial follicle assembly in offspring ovaries from zearalenone-exposed mothers involves reduced mitochondrial activity and altered epigenetics in oocytes

Abstract: Previous works have shown that zearalenone (ZEA), as an estrogenic pollutant, has adverse effects on mammalian folliculogenesis. In the present study, we found that prolonged exposure of female mice to ZEA around the end of pregnancy, caused severe impairment of primordial follicle formation in the ovaries of newborn mice and altered the expression of many genes in oocytes as revealed by scRNA-seq.These changes were associated with morphological and molecular alterations of mitochondria, increased autophagic m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…Zearalenone is one of the most prevalent mycotoxins globally; the Food and Agriculture Organization (FAO) estimated that 25% of crop production worldwide per year is contaminated with mycotoxins, and ZEN was detected in more than 62% of corn samples in the Asia-Pacific region in 2020. , Recent studies have shown that ZEN can be rapidly absorbed and metabolized by the gastrointestinal tract and distributed to different organs after ZEN ingestion by animals, and can even be transferred from the maternal body to breast milk. Numerous studies have shown that ZEN and its metabolites can cause toxic poisoning in animals, resulting in, for example, severe hepatotoxicity and reproductive toxicity. Previously, our studies have shown that maternal exposure to ZEN increased DNA damage, apoptosis, and impacted on mitochondrial activity, which is associated with the impaired primordial follicle assembly in ovaries of newborn pups. ,, However, very few studies have examined the effect of ZEN transmitted through maternal breast milk on follicular development in offspring.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Zearalenone is one of the most prevalent mycotoxins globally; the Food and Agriculture Organization (FAO) estimated that 25% of crop production worldwide per year is contaminated with mycotoxins, and ZEN was detected in more than 62% of corn samples in the Asia-Pacific region in 2020. , Recent studies have shown that ZEN can be rapidly absorbed and metabolized by the gastrointestinal tract and distributed to different organs after ZEN ingestion by animals, and can even be transferred from the maternal body to breast milk. Numerous studies have shown that ZEN and its metabolites can cause toxic poisoning in animals, resulting in, for example, severe hepatotoxicity and reproductive toxicity. Previously, our studies have shown that maternal exposure to ZEN increased DNA damage, apoptosis, and impacted on mitochondrial activity, which is associated with the impaired primordial follicle assembly in ovaries of newborn pups. ,, However, very few studies have examined the effect of ZEN transmitted through maternal breast milk on follicular development in offspring.…”
Section: Discussionmentioning
confidence: 94%
“…Previously, our studies have shown that maternal exposure to ZEN increased DNA damage, apoptosis, and impacted on mitochondrial activity, which is associated with the impaired primordial follicle assembly in ovaries of newborn pups. 17,19,33 However, very few studies have examined the effect of ZEN transmitted through maternal breast milk on follicular development in offspring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, it was exemplified that ZEN decreased the expression of oocyte-specific genes in germ cells, such as Lhx8 , Nobox , Sohlh2 , and Figla , increased the number of TUNEL positive cells, and reduced the number of germ cells in the ovaries of neonatal mice in vitro. ZEN also decreased mitochondrial activity, elevated autophagy levels, and altered the histone acetylation level of oocytes during primordial follicle formation . The previous study showed that ZEN exposure affected germ cell and granulosa cell development and impacted the ovarian reserve through Hippo and RIG-I receptor signaling pathways. , On the other hand, ZEN exposure would seriously reduce the expression of meiosis-related genes and result in a significant increase of DNA double-strand breaks (DSBs) in germ cells; at the same time, the aberrant morphologic features and cell cycle arrest were discovered. , Therefore, ZEN exposure has brought about severe ovarian toxicity, and the search for effective rescue agents is urgent.…”
Section: Introductionmentioning
confidence: 97%
“…19 ZEN also decreased mitochondrial activity, elevated autophagy levels, and altered the histone acetylation level of oocytes during primordial follicle formation. 20 The previous study showed that ZEN exposure affected germ cell and granulosa cell development and impacted the ovarian reserve through Hippo and RIG-I receptor signaling pathways. 21,22 On the other hand, ZEN exposure would seriously reduce the expression of meiosisrelated genes and result in a significant increase of DNA double-strand breaks (DSBs) in germ cells; 23 at the same time, the aberrant morphologic features and cell cycle arrest were discovered.…”
Section: Introductionmentioning
confidence: 99%